Global Emergency Medicine: A Review of the Literature from 2018. (22nd August 2019) - Trehan, Indi; Osei‐Ampofo, Maxwell; Balhara, Kamna S.; Hexom, Braden J.; Kivlehan, Sean M.; Modi, Payal; Pousson, Amelia Y.; Selvam, Anand; Quao, Nana Serwaa A.; Cho, Daniel K.; Becker, Torben K.; Levine, Adam C.; et al.
Abstract: Objectives: The Global Emergency Medicine Literature Review (GEMLR) conducts a systematic annual search of peer‐reviewed and gray literature relevant to global emergency medicine (EM) to identify, review, and disseminate the most rigorously conducted and widely relevant research in global EM. Methods: An electronic search of PubMed, a comprehensive retrieval of articles from specific journals, and search of the gray literature were conducted. Title and abstracts retrieved by these searches were screened by a total of 22 reviewers based on their relevance to the field of global EM, across the domains of disaster and humanitarian response (DHR), emergency care in resource‐limited settings (ECRLS), and emergency medicine development (EMD). All articles that were deemed relevant by at least one reviewer, their editor, and the managing editor underwent formal scoring of overall methodologic quality and importance to global EM. Two independent reviewers scored all articles; editors provided a third score in cases of widely discrepant scores. Results: A total of 19, 102 articles were identified by the searches and, after screening and removal of duplicates, a total of 517 articles underwent full review. Twenty‐five percent were categorized as DHR, 61% as ECRLS, and 15% as EMD. Inter‐rater reliability testing between the reviewers revealed a Cohen's kappa score of 0.213 when considering the complete score or 0.426 when excluding the more subjective half of the score. A total of 25 articles scored higher than 17.5 of 20; these were selected for a full summary and critique. Conclusions: In 2018, the total number of articles relevant to global EM that were identified by our search continued to increase. Studies and reviews focusing on pediatric infections, several new and traditionally underrepresented topics, and landscape reviews that may help guide clinical care in new settings represented the majority of top‐scoring articles. A shortage of articles related to the development of EM as a specialty was identified.